2007
DOI: 10.1097/jsm.0b013e31815b187d
|View full text |Cite
|
Sign up to set email alerts
|

Combined Tool Approach is 100% Successful for Emergency Football Face Mask Removal

Abstract: Sports medicine professionals must be prepared with appropriate tools and techniques to efficiently remove the face mask from an injured football player's helmet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 8 publications
1
40
0
Order By: Relevance
“…An unconscious athlete who is wearing a helmet and face mask will require immediate airway intervention, such as removal of a mouthguard and a jaw-thrust maneuver before or during face-mask removal. Removing a face mask also takes time, and as indicated previously, 29 can be rife with its own complications and delays.…”
Section: Limitationsmentioning
confidence: 99%
“…An unconscious athlete who is wearing a helmet and face mask will require immediate airway intervention, such as removal of a mouthguard and a jaw-thrust maneuver before or during face-mask removal. Removing a face mask also takes time, and as indicated previously, 29 can be rife with its own complications and delays.…”
Section: Limitationsmentioning
confidence: 99%
“…Whereas it took more than 10 seconds longer on average to remove the Riddell 360 helmet, the times for face-mask removal using quick-release technology in this helmet were improved dramatically over times reported for removal with a cordless screwdriver 9,11 or when cutting a loop strap is required. 14 Helmet manufacturers should consider incorporating full quick-release face-mask designs into any helmets that do not possess the technology and should design all future helmets with this feature. Finally, researchers should continue to examine the effects of helmet designs on viable emergency airway support, as some investigators have explored inserting a pocket mask beneath the face mask 9,15 and using airway adjuncts in a simulation-manikin research model.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, many investigators have examined questions related to equipment removal and cervical spine motion, [1][2][3] airway access techniques, 4,5 and techniques and efficiency of face-mask removal. [6][7][8][9][10][11][12][13] Evidence has suggested that airway access can be obtained in the football-helmeted athletes without the removal of the face mask, ultimately reducing motion of the cervical spine often associated with face-mask removal. 4,5,14 However, the National Athletic Trainers' Association 15 and the InterAssociation Task Force for the Appropriate Care of the Spine-Injured Athlete 16 advocate full removal of the football face mask under all circumstances.…”
mentioning
confidence: 99%
“…However, the efficiency of facemask removal and the extent to which cervical spinal motion is generated by using these tools have been questioned considerably. 8,9,11,13,14 Gale et al 12 and Copeland et al 6 suggested a combined-tool approach, indicating that using a cordless screwdriver and the FM Extractor when screws fail is fast, easy, and reliable. More recently, Toler et al 14 reported that access was quicker and helmet motion was less when using the Revolution IQ (Riddell Sports, Inc, Elyria, OH) helmets equipped with the Quick Release (QR) Face Guard Attachment System (Riddell Sports, Inc) than when using helmets that require removing clips with a cordless screwdriver.…”
mentioning
confidence: 99%
See 1 more Smart Citation